Developing an evidence-based fall prevention curriculum for community health workers - Julie Ann St. John; Tiffany E Shubert; Matthew Lee eSmith; Cherie A. Rosemond; Doris eHowell; Christopher eBeaudoin; Marcia Gail Ory (Frontiers Media S.A., 2015)
*